2006
DOI: 10.1002/j.2161-0045.2006.tb00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Practice and Research in Career Counseling and Development-2005

Abstract: This article reviews professional literature published in 2005 related to career counseling and career development. The literature is divided into 4 broad areas: professional issues, career theory and concepts, career interventions and practice, and career assessment and technology. The authors summarize and discuss the implications of the findings for career counseling practice and research.Writing this review provided constant discovery. The career field is large, diverse, and specialized, and authors who co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 199 publications
0
9
0
1
Order By: Relevance
“…To achieve a dialogue, the thoughts and feelings of students with respect to their work experiences must be given a central place in the conversation (Philip, 2001; Bardick, Bernes, Magnusson & Witko, 2006). The dialogue cannot be a one-off discussion but must be a form of ongoing support (Riverin-Simard, 2000;Harrington & Harrigan, 2006). Students, however, do not seem to participate in a career dialogue willingly; they are hardly motivated to participate in reflective activities about their careers when these are prescribed as part of the curriculum (Law, Meijers & Wijers, 2002;Mittendorff, 2010).…”
Section: A Career Learning Environment In Educationmentioning
confidence: 99%
“…To achieve a dialogue, the thoughts and feelings of students with respect to their work experiences must be given a central place in the conversation (Philip, 2001; Bardick, Bernes, Magnusson & Witko, 2006). The dialogue cannot be a one-off discussion but must be a form of ongoing support (Riverin-Simard, 2000;Harrington & Harrigan, 2006). Students, however, do not seem to participate in a career dialogue willingly; they are hardly motivated to participate in reflective activities about their careers when these are prescribed as part of the curriculum (Law, Meijers & Wijers, 2002;Mittendorff, 2010).…”
Section: A Career Learning Environment In Educationmentioning
confidence: 99%
“…Other integrative theories include Savickas' (2001) four level model, which builds on McAdams' earlier work, incorporating personality dispositions, self-regulatory career concerns, career narratives and a process for continuity and change in career development. Systems Theory Framework (STF) (McMahon, 2005) provides a metatheoretical view of career development (Harrington & Harrigan, 2006;Patton, 2007) by bringing together modern and post-modern career theories (McMahon & Watson, 2007). Pryor and Bright (2003a;2003b;Bright & Pryor, 2007) extended systems thinking by proposing the Chaos Theory of Careers (CTC), which holds that an individual's career is a complex system, capable of self-organising but at the same time susceptible to unpredictable change (Pryor & Bright, 2007a).…”
Section: Constructivist and Postmodern Approaches To Careersmentioning
confidence: 99%
“…The number of articles and journals represented in the reviews has grown over time. Each one of those 25 reviews provided a brief summary of the content of articles by topic, as well as a commentary on the nature of the literature published that year (Arbona, 2000;Bikos, Dykhouse, Boutin, Gowen, & Rodney, 2013;Chope, 2008;Cook, 1991;Creager, 2011;Dagley & Salter, 2004;Erford & Crockett, 2012;Flores et al, 2003;Guindon & Richmond, 2005;Harrington & Harrigan, 2006;Hartung, 2010;Jepsen, 1992;Luzzo & MacGregor, 2001;Niles, 1997;Patton & McIlveen, 2009;Salomone, 1993;Savickas, 1989;Spokane & Hawks, 1990;Stoltz-Loike, 1996;Subich, 1994;Swanson & Parcover, 1998;Tien, 2007;Walsh & Srsic, 1995;Whiston & Brecheisen, 2002;Young & Chen, 1999). In reviewing past CDQ annual reviews, we identified some noteworthy trends.…”
mentioning
confidence: 99%